2010
DOI: 10.1088/0957-4484/21/25/255706
|View full text |Cite
|
Sign up to set email alerts
|

Facile hydrothermal synthesis of porous TiO2nanowire electrodes with high-rate capability for Li ion batteries

Abstract: Anatase TiO(2) nanowires were successfully synthesized using a low-temperature hydrothermal treatment on as-prepared one-dimensional (1D) hydrogen titanate nanowires (H(2)Ti(3)O(7)) at 180 degrees C. The anatase TiO(2) nanowires were porous in nature with a high specific surface area. These nanowires were characterized using transmission electron microscopy (TEM), high-resolution TEM, x-ray powder diffraction, Raman spectroscopy, and Brunauer-Emmett-Teller (BET) measurements. The topochemical phase transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…The capacity of 203.9 mAh g À1 was higher than the theoretical value of 168 mAh g À1 for TiO 2 materials. However, such values were observed in earlier reports and attributed to the high insertion coefficient for the first cycle, the surface storage mechanism (pseudo-capacities) and possible contribution from carbon materials [56,57]. As clearly shown in Figure S6 in the supporting information, the capacity contribution from carbon component in the hybrid co-aerogel cannot be neglected.…”
Section: Monolithic Lithium Ion Battery Performancementioning
confidence: 62%
“…The capacity of 203.9 mAh g À1 was higher than the theoretical value of 168 mAh g À1 for TiO 2 materials. However, such values were observed in earlier reports and attributed to the high insertion coefficient for the first cycle, the surface storage mechanism (pseudo-capacities) and possible contribution from carbon materials [56,57]. As clearly shown in Figure S6 in the supporting information, the capacity contribution from carbon component in the hybrid co-aerogel cannot be neglected.…”
Section: Monolithic Lithium Ion Battery Performancementioning
confidence: 62%
“…[65][66][67][68] Shim et al 46 have successfully obtained porous TiO 2 nanowires from 1D hydrogen titanate nanowires (H 2 Ti 3 O 7 Á nH 2 O) using a facile low-temperature hydrothermal treatment. As the precursor, the hydrogen titanate nanowires were¯rst synthesized using a hydrothermal treatment in an alkaline environment.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…Han et al 37 reported that the porous SnO 2 nanowire bundles synthesized in high yield through a simple solution approach could be maintained at discharge capacity of 530 mAh g À1 after 20 cycles, which are superior to porous SnO 2 microtubes as well as the polycrystalline SnO 2 solid nanowires. 113,114 Shim et al 46 evaluated the capacity of porous anatase TiO 2 nanowires and found that the value can reach 145 mAh g À1 at 1 C and 115 mAh g À1 at 20 C after 500 cycles, revealing an excellent cycling performance and superior rate capabilities compared with the H 2 Ti 3 O 7 nanowires. Afterward, Wang et al 115 also developed a facile and rapid two-step synthesis route for porous wire-like TiO 2 nanostructures as anodes for Li-ion batteries, exhibiting superior high speci¯c capacity (206 mAh g À1 at 0.2 C) and remarkable rate capability (167:1 AE 0:7 and 116:1 AE 1:1 mAh g À1 at 0.5 C and 5 C, respectively).…”
Section: Rechargeable Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…nanostructured materials have many obvious advantages in comparison with respective counterparts with microcosmic sizes, such as high rate performance, large capacity and long cycle life, due to the larger specific surface area, shorter transport length for both electronic and Li + ions and better accommodation of the strain during Li insertion/extraction[7][8][9][10][11][12][13][14][15] , so it is receiving increasing interests for the application in lithium ion batteries. Inspired by this, we attempt to synthesize H 2 Ti 12 O 25 with specific nanostructures via hydrothermal reaction following heat treatment to improve its electrochemical properties.…”
mentioning
confidence: 99%